The Impact of Heat-Moisture Treatment on the Properties of Musa paradisiaca L. Starch and Optimization of Process Variables - Maria José Missão Cordeiro; Cristiane Martins Veloso; Leandro Soares Santos; Renata Cristina Ferreira Bonomo; Márcio Caliari; Rafael da Costa Ilhéu Fontan (Food Technology and Biotechnology, 2018)
Starch stability under the processing conditions can be improved by modifying the granule structure using chemical and/or physical processes. The effect of heat-moisture treatment (HMT) on the physicochemical, morphological, pasting and thermal properties of green banana (Musa paradisiaca L.) starch was investigated. To analyze the changes in starch properties due to the combined effect of the process variables, time (h), moisture (%), and temperature (°C) were considered as independent variables using a central composite rotatable design. The native starch extracted using ammonium hydroxide as an antioxidant contained 80.4 % total carbohydrates, 53.7 % apparent amylose, 11.46 % moisture, and other constituents (ash, protein, lipids), which accounted for less than 1 %. The granule morphology was affected by the moisture and temperature used in HMT. A and B type X-ray diffraction patterns were observed in the native and modified starch. Mathematical models that describe the behaviour of modified starch properties as a function of the evaluated parameters were obtained. Then variables time and temperature significantly affected the physicochemical, rheological and digestibility properties of starch.